2013
DOI: 10.1177/1057083713512836
|View full text |Cite
|
Sign up to set email alerts
|

Important Others

Abstract: The music education profession needs the best and brightest students with potential to be excellent music educators to choose music education as a profession. Past research has identified several influences in the career choice of music educators, including important others in students’ lives. In particular, high school music teachers appear to influence the career choices of students who choose to major in music education. The present study surveyed a purposeful sample of high school music teachers to help il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Previous research has shown that the music teacher is one of the most critical figures in guiding a student toward the profession (Bergee et al, 2001; Fredrickson & Burton, 2005; Gillespie & Hamann, 1999; Madsen & Kelly, 2002; Rickels et al, 2010; Rickels et al, 2013; Thornton, 2013, 2014; Thornton & Bergee, 2008). It was encouraging, therefore, that students in programs taught by over half of the respondents in this study were provided with opportunities that helped them explore the music education profession as a viable career option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that the music teacher is one of the most critical figures in guiding a student toward the profession (Bergee et al, 2001; Fredrickson & Burton, 2005; Gillespie & Hamann, 1999; Madsen & Kelly, 2002; Rickels et al, 2010; Rickels et al, 2013; Thornton, 2013, 2014; Thornton & Bergee, 2008). It was encouraging, therefore, that students in programs taught by over half of the respondents in this study were provided with opportunities that helped them explore the music education profession as a viable career option.…”
Section: Discussionmentioning
confidence: 99%
“…Providing teaching opportunities and demonstrating job satisfaction were suggested as strategies for recruiting future music teachers. Thornton (2013Thornton ( , 2014) studied a purposive sample of high school music teachers to illuminate the beliefs and actions of "important others" on student choice of a career in music education. Thornton found that music skills were highly valued by both in-service music teachers and their students as an indicator of potential success in the music teaching profession.…”
mentioning
confidence: 99%
“…Extant research has long recognized the influential role that music teachers play in students’ decisions to pursue music education as a field of study and future profession (Bergee, 1992; Bergee et al, 2001; Bright, 2006; Davis, 1990; Fredrickson & Burton, 2005; Gillespie & Hamann, 1999; Hamann & Cutietta, 1996; Hellman, 2008; Isbell, 2008; Kantorski, 2004; Madsen & Kelly, 2002; Rickels et al, 2010, 2013; Thornton & Bergee, 2008; White, 1967; Wilcox, 2000). Recent investigations by Austin, Isbell, and Russell (2012); Draves (2012); Taylor and Hallam (2011); and Thornton (2015) add to this body of research, further underscoring the positive impact that music teachers have on their students’ career decisions.…”
Section: Music Teacher Influencementioning
confidence: 95%
“…In-service music educators also named teachers among those individuals and/or experiences inspiring a career in music. Elementary and secondary music educators surveyed by Thornton (2015) believed teachers were “moderate” to “significant” influences on their students’ decision to pursue a career in music education, more so than other named individuals (Thornton, 2015, p. 101). Even those offering studio instruction as a second career recalled positive interactions with or reported support or encouragement from former and current musical mentors (Taylor & Hallam, 2011).…”
Section: Music Teacher Influencementioning
confidence: 99%
See 1 more Smart Citation